OSA, Short Sleep Duration, and Their Interactions With Sleepiness and Cardiometabolic Risk Factors in Adults: The ELSA-Brasil Study - Drager, Luciano F; Santos, Ronaldo B; Silva, Wagner A; Parise, Barbara K; Giatti, Soraya; Aielo, Aline N; Souza, Silvana P; Furlan, Sofia F; Lorenzi-Filho, Geraldo; Lotufo, Paulo A; Bensenor, Isabela M (Chest, 2019)
OSA and short sleep duration (SSD) are frequently associated with daytime symptoms and cardiometabolic deregulation. However, the vast majority of studies addressing OSA have not evaluated SSD, and vice versa. Our aim was to evaluate the association of OSA, SSD, and their interactions with sleepiness and cardiometabolic risk factors in a large cohort of adults. Consecutive subjects from the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil) participated in clinical evaluations, sleep questionnaires, home sleep monitoring, and actigraphy. OSA was defined as an apnea-hypopnea index ≥ 15 events/hour. SSD was defined by a mean sleep duration < 6 h. Data from 2,064 participants were used in the final analysis (42.8% male; mean age, 49 ± 8 years). The overall frequency of OSA and SSD were 32.9% and 27.2%, respectively. Following an adjustment for multiple confounding factors, excessive daytime sleepiness was independently associated with SSD (OR, 1.448; 95% CI, 1.172-1.790) but not with OSA (OR, 1.107; 95% CI, 0.888-1.380). The SSD interaction with OSA was not significant. Prevalent obesity (OR, 3.894; 95% CI, 3.077-4.928), hypertension (OR, 1.314; 95% CI, 1.035-1.667), and dyslipidemia (OR, 1.251; 95% CI, 1.006-1.555) were independently associated with OSA but not with SSD. Similarly, the interactions of OSA with SSD were not significant. An additional analysis using < 5 h for SSD or continuous sleep duration did not change the lack of association with the cardiometabolic risk factors. Objective SSD but not OSA was independently associated with daytime sleepiness. By contrast, OSA, but not SSD, was independently associated with obesity, hypertension, and dyslipidemia.